2021
DOI: 10.3389/fped.2021.760070
|View full text |Cite
|
Sign up to set email alerts
|

Hematuria as an Early Sign of Multisystem Inflammatory Syndrome in Children: A Case Report of a Boy With Multiple Comorbidities and Review of Literature

Abstract: Introduction: While the clinical course of SARS-CoV-2 infection seems to be milder or asymptomatic within the pediatric population, growing attention has been laid to the rare complication elicited by virus, multisystem inflammatory syndrome in children temporarily associated with COVID-19 (MIS-C). Published definition and criteria of MIS-C include persistent fever, multisystem involvement, and elevated markers of inflammation, without obvious microbial inflammation or other plausible diagnosis. However, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…Generally speaking, while the onset of MISC observed in our study resembled the onset symptoms described in cases reported in the literature, the clinical evolution of our patients was found to be relatively favorable (17). Early multidisciplinary diagnosis and the immediate use of immunomodulatory and anticoagulant therapies, as well as the inotropic support given to patients with severe cardiac dysfunction or with capillary leaks, certainly played a role in preventing other organ damage, such as AKI (26).…”
Section: Discussionsupporting
confidence: 79%
“…Generally speaking, while the onset of MISC observed in our study resembled the onset symptoms described in cases reported in the literature, the clinical evolution of our patients was found to be relatively favorable (17). Early multidisciplinary diagnosis and the immediate use of immunomodulatory and anticoagulant therapies, as well as the inotropic support given to patients with severe cardiac dysfunction or with capillary leaks, certainly played a role in preventing other organ damage, such as AKI (26).…”
Section: Discussionsupporting
confidence: 79%
“…It is worth underlying that the literature also provides cases of PIMS-TS with haematuria as an early sign of the disease [12] or diarrhoea and fever as the only symptoms presented by the patient [13]. Those cases confirm the need for the conduction of an extended diagnostic process for each child reporting to the hospital, even when the symptoms are not characteristic and specific for PIMS-TS.…”
Section: Acute Rheumatic Fevermentioning
confidence: 70%
“…PIMS-TS should be differentiated with many paediatric conditions, such as Kawasaki disease, rheumatic fever, or appendicitis (more information in Table 3) [10][11][12][13][14][15].…”
Section: Acute Rheumatic Fevermentioning
confidence: 99%
“…Cardiovascular MRI should have been at least considered, even though direct tissue examination remains the diagnostic reference standard. The indirect statement in the article that thrombocyte levels can rule out Kawasaki disease at “day 7” is also misleading, as thrombocytosis in Kawasaki disease is often seen in the second or third week of illness ( 1 , 14 ).…”
Section: Subsections Relevant To the Subjectmentioning
confidence: 99%
“…Recently, we encountered an article that describes hematuria as the early onset of multisystem inflammatory syndrome in children (MIS-C) ( 1 ). Upon further analysis, we found some inconsistencies in the commented article, which we outlined in the following article.…”
Section: Introductionmentioning
confidence: 99%